1963
DOI: 10.1002/jsfa.2740141207
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value of dried infant milk foods based on buffalo milk

Abstract: 877solution gradually approach a level above which little adsorption occurs even if the concentration increases. The adsorption of phosphate cannot be attributed to any single mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1968
1968
2000
2000

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Earlier studies on soy-whey powder showed that free fatty acids and peroxide values increased and available lysine decreased during storage [1,2]. Flavour changes were minimal in soy-whey powder stored in polyethylene bags at room temperature [3].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies on soy-whey powder showed that free fatty acids and peroxide values increased and available lysine decreased during storage [1,2]. Flavour changes were minimal in soy-whey powder stored in polyethylene bags at room temperature [3].…”
Section: Introductionmentioning
confidence: 99%